Determine the Efficacy and Safety of PCNL in Solitary Functioning Kidney - Muhammad Abdul Rauf, Abdul Rauf, Fazal-Ur-Rehman Khan, Muhammad Yahya Hasan, Muhammad Tayyab Naeem (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the efficacy and safety of PCNL in solitary functioning kidney. Study design: Descriptive case series study. Place and duration of study: This study was conducted at the Department of Urology, Shaikh Zayed Hospital, Lahore from October 21, 2020 to April 21, 2021. Materials and Methods: A total of 60 patients were included in this study which was carried out at Shaikh Zayed Hospital, Lahore at Urology Department. Results: Efficacy of PCNL in solitary functioning kidney was in 93.3% (n=56) patients. Safety of PCNL in solitary functioning kidney was in 85% (n=51) patients. Conclusion: The effectiveness and safety of PCNL in patients with a single functional kidney and discovered that 93.3% (n=56) of patients demonstrated efficacy, and 85% (n=51) of patients shown safety. Keywords: Urolithiasis, Extracorporeal shockwave lithotripsy, Potential consequence of percutaneous nephrolithotomy, Solitary functional kidneys.